The influence of parents' socioeconomic status on the learning outcomes of 4th grade students at UPT SPF SDN Baddoka Makassar City - Hamzah, Rahma Ashari; Jumrah, Abrina Maulidnawati; Syam, Nur; Syam, Syam (Universitas Nusantara PGRI Kediri, 2023)
The Influence of Parents' Socioeconomic Status on the Learning Outcomes of 4th Grade Students at UPT SPF SDN Baddoka, Makassar City. This research aimed to determine the influence of parents' socioeconomic status on the learning outcomes of 4th-grade students at UPT SPF SDN Baddoka, Makassar City. The study used a quantitative research design with an ex post facto type of research. The population of this study consists of all students in class IVa at UPT SPF SDN Baddoka, Makassar City, totaling 28 students, while the sample comprises 20 students from class IVa using a non-random sampling technique (purposive sampling). Data collection techniques and instruments used are questionnaires and documentation, in the form of student learning outcomes, to identify the influence of parent's socioeconomic status on students' learning outcomes. Data analysis techniques include descriptive statistical analysis and inferential statistical analysis (normality test, linearity test, and hypothesis test). The result of the t-test calculation shows a significant value of parent's socioeconomic status at 0.003 < 0.05 (3.025 > 2.101), which means that H0 is rejected, and Ha is accepted, indicating that there is an influence of parent's socioeconomic status on the learning outcomes of 4th-grade students at UPT SPF SDN Baddoka, Makassar City. In conclusion, parent's socioeconomic status has a positive and significant influence on students' learning outcomes.